Protein-C deficiency presenting as Pulmonary embolism and Deep vein thrombosis: A case report - Fatema, Kaniz; Ahmed, Borhan Uddin; Rahman, Mohammad Mahfuzur (Pulse, 2024)
Plasma protein-C is a naturally occurring anticoagulant and its deficiency, either homozygous or heterozygous, predisposes the individual to a state of thrombosis, particularly venous thromboembolism, and manifests as deep venous thrombosis (DVT), pulmonary embolism (PE), myocardial infarction (MI), or stroke. Protein C exerts anticoagulatory effects by inactivating factors V and VIII. Hereditary protein C deficiency is inherited as an autosomal dominant disorder. Homozygous individuals usually develop purpura fulminans as newborns; heterozygous protein C-deficient individuals are at increased risk for venous thrombosis and pulmonary embolism. We describe a young patient with protein-C deficiency who experienced recurrent pulmonary embolism as well as deep vein thrombosis due to thrombotic occlusion without underlying major risk factors. Pulse Vol.16, 2024 P: 43-46